2015
DOI: 10.1097/igc.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Long Follow-up of Patients With Locally Advanced Cervical Cancer Treated With Concomitant Chemobrachyradiotherapy With Cisplatin and Ifosfamide Followed by Consolidation Chemotherapy

Abstract: Chemobrachyradiotherapy regimen followed by consolidation chemotherapy described in this article is a valuable treatment option for LACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Petrić Miše et al 11 and Jelavić et al 12 reported encouraging results of four adjuvant cycles of cisplatin and ifosfamide chemotherapy after completion of concurrent chemoradiotherapy in an attempt to improve distant-relapse–free survival. In a randomized trial, Wong et al 13 showed improvement in overall survival after administration of adjuvant chemotherapy with epirubicin at 90 mg/m 2 compared with pelvic radiotherapy and no additional chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Petrić Miše et al 11 and Jelavić et al 12 reported encouraging results of four adjuvant cycles of cisplatin and ifosfamide chemotherapy after completion of concurrent chemoradiotherapy in an attempt to improve distant-relapse–free survival. In a randomized trial, Wong et al 13 showed improvement in overall survival after administration of adjuvant chemotherapy with epirubicin at 90 mg/m 2 compared with pelvic radiotherapy and no additional chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…However, these indicators are not definitive criteria for determining which patients respond to CCRT and which patients need further treatment. Confirming worse survival patients during treatment by the response to CCRT may be predicted earlier and alternative initial treatment schedule ( 23 , 24 ). Therefore, some indicators that can be measured by MRI easily and non-invasively during the treatment, such as TVRR, have received increasing attention from researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Although poorer prognosis in patients with certain conditions, such as large tumor size, adenocarcinoma, or positive PLN metastasis after primary surgery, have been reported [4,7], there are no confirmed criteria for determining which patients need additional treatment; nor is there enough evidence to alter recent treatment guidelines for high-risk patients. Nevertheless, previous studies of patents with locally advanced cervical cancer, from our center and others, have consistently reported that consolidation chemotherapy after primary CCRT might enhance local control and eradicate distant micrometastases [20-23]. A phase-II study that enrolled high-risk early-stage cervical cancer patients as well as locally advanced patients concluded that consolidation chemotherapy had low efficacy [24].…”
Section: Discussionmentioning
confidence: 99%